2011
DOI: 10.4297/najms.2011.3428
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent pneumothorax: A rare complication of miliary tuberculosis

Abstract: Context:Recurrent pneumothorax is common in cavitory pulmonary tuberculosis, but it is extremely rare in miliary tuberculosis.Case Report:A 25 year old female patient presented to us with the complains of shortness of breath since 3 days. She was also having fever and cough since 3 months. Chest roentgenogram (PA view) on admission showed a left sided pneumothorax with miliary mottling. An intercostals tube drainage was done on the left side resulting in relief of symptoms. Two days post intercostals tube drai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
(6 reference statements)
0
11
0
Order By: Relevance
“…Although this disease is caused by a bacterium and not a virus, the resulting x-ray picture of localised calcifications is well recognised and is termed miliary tuberculosis. 19,20 It is also possible that the risk of developing complications of Zika may reflect the genetic differences between the sufferers and the general population. But at the present stage of our knowledge there is no indication of what particular differences might be important.…”
Section: The Complications Of Zika Infectionmentioning
confidence: 99%
“…Although this disease is caused by a bacterium and not a virus, the resulting x-ray picture of localised calcifications is well recognised and is termed miliary tuberculosis. 19,20 It is also possible that the risk of developing complications of Zika may reflect the genetic differences between the sufferers and the general population. But at the present stage of our knowledge there is no indication of what particular differences might be important.…”
Section: The Complications Of Zika Infectionmentioning
confidence: 99%
“…The reported frequency of occurrence of pneumothorax in tuberculosis is 1.5% 4 . Air leak and pneumothorax is a well‐known phenomenon in adult‐onset cavitary tuberculosis but is very rare in miliary tuberculosis 5 . In children, it has been reported that miliary tuberculosis may very rarely present with unilateral or bilateral pneumothorax 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The recognition of pneumothorax might be delayed in these children as the clinical features may be masked by the baseline respiratory distress present in miliary tuberculosis. 5 Delayed recognition might be life-threatening. Miliary tuberculosis with spontaneous pneumothorax can be treated mostly with intercostal tube drainage.…”
Section: Malignancies (Metastatic Carcinoma Bronchoalveolar Carcinoma)mentioning
confidence: 99%
“…[9] The characteristic finding of bilateral pneumothorax may point more toward LCH, but there are a few reports of miliary tuberculosis also presenting with pneumothorax, further complicating the clinical and radiological approach to diagnosis. [10][11][12] Coexistent pulmonary LCH and tuberculosis can occur and has been reported in adults but not in children. [13] Every effort should be made to prove the diagnosis of LCH by histopathological diagnosis, especially before starting chemotherapy.…”
Section: Discussionmentioning
confidence: 99%